Origin of atmospheric aerosols at the Pierre Auger Observatory using studies of air mass trajectories in South America - Aab, A.; Abreu, Pedro; Aglietta, Marco; Ahlers, Markus; Ahn, E. J.; Albuquerque, I. F. M.; Allekotte, I.; Allen, J.; Allison, P.; Almela, A.; Castillo, J. Alvarez; Alvarez-Muniz, Jaime; et al. (Atmospheric Research, 2014)
The Pierre Auger Observatory is making significant contributions towards understanding the nature and origin of ultra-high energy cosmic rays. One of its main challenges is the monitoring of the atmosphere, both in terms of its state variables and its optical properties. The aim of this work is to analyse aerosol optical depth tau(a)(z) values measured from 2004 to 2012 at the observatory, which is located in a remote and relatively unstudied area of Pampa Amarilla, Argentina. The aerosol optical depth is in average quite low - annual mean tau(a)(3.5 km) similar to 0.04 - and shows a seasonal trend with a winter minimum - tau(a)(3.5 km) - 0.03 -, and a summer maximum - tau(a)(3.5 km) similar to 0.06 -, and an unexpected increase from August to September tau(a)(35 km) similar to 0.055. We computed backward trajectories for the years 2005 to 2012 to interpret the air mass origin. Winter nights with low aerosol concentrations show air masses originating from the Pacific Ocean. Average concentrations are affected by continental sources (wind-blown dust and urban pollution), whilst the peak observed in September and October could be linked to biomass burning in the northern part of Argentina or air pollution coming from surrounding urban areas. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Cosmic ray; Aerosol; Air masses; Atmospheric effect; HYSPLIT; GDAS